Origin of the Functional Distinctiveness of NF-κB/p52 - Ghosh, Gourisankar; Wang, Vivien Ya-Fan (Frontiers in Cell and Developmental Biology, 2021)
The transcription regulators of the NF-κB family have emerged as a critical factor affecting the function of various adult tissues. The NF-κB family transcription factors are homo- and heterodimers made up of five monomers (p50, p52, RelA, cRel and RelB). The family is distinguished by sequence homology in their DNA binding and dimerization domains, which enables them to bind similar DNA response elements and participate in similar biological programs through transcriptional activation and repression of hundreds of genes. Even though the family members are closely related in terms of sequence and function, they all display distinct activities. In this review, we discuss the sequence characteristics, protein and DNA interactions, and pathogenic involvement of one member of family, NF-κB/p52, relative to that of other members. We pinpoint the small sequence variations within the conserved region that are mostly responsible for its distinct functional properties.